Improving Students' Critical Thinking Skills through Digital Storytelling on Narrative Text - Wiwikananda, Sasi Kirana Sugi; Susanti, Arik (Pioneer: Journal of Language and Literature, 2022)
This study investigates whether or not students' critical thinking skills can be improved through the use of digital storytelling. It was a pre-experimental design in which one group was tested twice, once before treatment was given and once after treatment had been administered. The instrument consisted of a test that included both multiple-choice questions and an essay test in order to evaluate the students' capacity for critical thinking after they had been exposed to narrative texts. Twenty students from a language class at one of the Islamic senior high schools in Bali, Indonesia, were the ones who took part in the study. In order to evaluate the growth of the students, the data were put through a paired sample t-test for analysis. The findings demonstrated that using digital storytelling to tell a story can strengthen students' ability to think critically. It was established that the mean score on the pre-test was 63.85, and the mean score on the post-test was 84.85, which indicates that there was an increase in performance. In addition, the significance value was 0.000, which was a number that was lower than 0.05. It meant that students' analytical and deductive reasoning abilities improved. It is strongly recommended, for the purposes of future research, to carry out studies using a significantly larger number of samples.